Umbilical Vessel Rupture Leading to Adverse Pregnancy Outcomes: Two Cases - He M; Zhao K; Huang J (International Journal of Women's Health)
MeiRong He,* KaiSun Zhao,* JianChun Huang Department of Obstetrics, The Second Nanning People’s Hospital (The Third Affiliated Hospital of Guangxi Medical University), Nanning, Guangxi, 530031, People’s Republic of China*These authors contributed equally to this workCorrespondence: JianChun Huang, Department of Obstetrics, The Second Nanning People’s Hospital, The Third Affiliated Hospital of Guangxi Medical University, No. 13, Dancun Road, Jiangnan District, Nanning City, Guangxi Zhuang Autonomous Region, People’s Republic of China, Tel +86 13207801809, Email huangjc3081@163.comObjective: This study aims to alert authors and readers to the possibility of spontaneous umbilical vessel rupture in cases of sudden changes in fetal heart rate or bloody amniotic fluid.Methods: We analyzed cases of spontaneous rupture of umbilical cord vessels at our hospital over the past three years. Two cases of patients who delivered at our hospital were analyzed, both of whom exhibited sudden changes in fetal heart rate during the prenatal period and subsequently underwent emergency cesarean sections. Intraoperatively, both cases revealed a succenturiate placenta with ruptured umbilical vessels and bleeding.Results: Both cases resulted in adverse pregnancy outcomes due to succenturiate placenta and bleeding from ruptured umbilical vessels, with pathological examination of the placenta confirming the clinical diagnosis.Conclusion: Enhancing the detection rate of prenatal ultrasound for placental membranacea and umbilical cord vessel abnormalities, coupled with timely intervention, is crucial for reducing perinatal mortality.Keywords: umbilical vessel abnormalities, succenturiate placenta, pregnancy outcomes